Protective efficacy of bivalent inactivated avian influenza subtype H9N2 and Newcastle disease vaccines commercially available in Bangladesh - Hossain, Md Riabbel; Tasnim, Shadia; Akter, Most Shahana; Pervin, Munmun; Begum, Jahan Ara; Chowdhury, Emdadul Haque; Parvin, Rokshana (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Low pathogenic avian influenza (LPAI) subtype H9N2 and Newcastle disease (ND) are the two major economic diseases worldwide. Continuous genetic evolution of both viruses raises concerns about potential vaccine failure under field conditions. The efficacy of commercially available bivalent inactivated vaccines in preventing ND and avian influenza subtype H9N2 in Bangladesh has not been comprehensively assessed. This study aimed to contribute crucial insights into the evaluated vaccine’s performance against local field strains and to contribute novel data to optimize poultry vaccination strategies in endemic regions. Materials and Methods: The experimental birds were divided into several groups and were vaccinated according to the manufacturer’s recommendation. Serum samples were collected at regular intervals. Antibody levels against H9N2 and ND virus (NDV) were assessed using hemagglutination inhibition and enzyme-linked immunosorbent assay tests, targeting each virus individually. Following the final booster dose, vaccinated and unvaccinated groups were challenged with locally circulating NDV and H9N2 AI virus strains. Results: Vaccinated chickens developed robust antibody responses, with titers progressively increasing after each booster and peaking following the final dose. Upon challenge with circulating strains of NDV and H9N2, the immunized birds exhibited no clinical signs of disease. Moreover, no detectable viral shedding of H9N2 was observed, and only minimal NDV shedding was detected in the vaccinated groups. Conclusion: Our study revealed that all three bivalent inactivated vaccines are effective against LPAI and ND in poultry and elicit a quick and robust antibody response. J. Adv. Vet. Anim. Res., 12(3): 916–928, September 2025 http://doi.org/10.5455/javar.2025.l953